Impact of metabolic syndrome on mean platelet volume and its relationship with coronary artery disease. (4th July 2019) - Nardin, Matteo; Verdoia, Monica; Barbieri, Lucia; De Luca, Giuseppe; ,
Abstract: Platelets represent one of the main actors involved in pathogenesis of coronary artery disease (CAD). Mean platelet volume (MPV) has been proposed as marker of platelet reactivity and thrombotic risk. However, still debated is whether higher MPV constitutes an independent determinant of CAD or just the consequence of an association with several cardiovascular risk factors. Therefore, the aim of the present study was to assess the impact of metabolic syndrome (MetS), on MPV and its relationship with angiographically defined CAD. Consecutive patients undergoing coronary angiography were included. Admission samples were collected for MPV and chemistry assessment. MetS was defined according to IDF-criteria. Significant CAD was defined as at least 1 vessel stenosis > 50%, while severe CAD as left main and/or 3-vessel disease, as evaluated by quantitative coronary angiography. We included 4730 patients, among them 2167 (45.8%) had MetS. Patients with MetS were older ( p  < 0.001), more often females ( p  < 0.001), and displayed higher BMI, higher prevalence of hypercholesterolemia, renal failure, hypertension, diabetes mellitus, history of myocardial infarction (MI), previous PCI ( p  < 0.001, respectively), previous CABG ( p  = 0.002), treatment with ACE inhibitors, ARB, beta-blockers, nitrates, statins, ASA, calcium channel blockers, diuretics ( p  < 0.001, respectively), higher values of glycemia, HbA1c, fibrinogen ( p  < 0.001, respectively), creatinine ( p  = 0.01), uric acid ( p  = 0.02), and lower values of hemoglobin ( p  = 0.001), total-cholesterol, LDL-cholesterol, and HDL-cholesterol ( p  < 0.001, respectively). MetS patients showed a higher prevalence of CAD ( p  = 0.002) and severe CAD ( p  = 0.01). MPV values were slightly higher in patients with MetS (10.91 ± 1.01 vs. 10.84 ± 1.03 fL, p  = 0.02), although MetS did not emerge as an independent predictor of higher MPV values (above 4 th quartile; adjusted OR OR[95%CI] = 1.01[0.84–1.22], p  = 0.93). When metabolic syndrome patients were analyzed according to MPV quartiles, higher MPV values did not result as an independent predictor of CAD (adjusted OR[95%CI] = 0.79[0.61–1.03], p  = 0.08) and severe CAD (adjusted OR[95%CI] = 0.82 [0.65–1.03], p  = 0.084). Results did not change when applying the new harmonized definition of MetS. This study shows that among patients undergoing coronary angiography MetS is not an independent predictor of higher MPV. Moreover, among MetS patients, larger-sized platelets are not associated to the prevalence and extent of CAD.